Justifying the use of structure-forming agents to increase storability of confectionery products with the foamy structure - N. B. Kondratev; O. S. Rudenko; E. V. Kazantsev; I. A. Belova; N. A. Petrova (Пищевые системы, 2023)
Confectionery products with the foamy structure such as pastila and zefir (Russian marshmallow-like confectioneries) are in demand among various consumer groups. The expansion of the range and sales markets requires ensuring quality of such products during their transportation, storage, as well as increasing their shelf life. The patterns of change in quality indicators allow establishing additional requirements for them to improve storability of such products. Moisture transfer processes are predominant during storage of confectionery products with the foamy structure and define their hardening or moistening. Therefore, it is necessary to evaluate the influence of various factors on quality indicators during storage of zefir. Studies have been carried out to determine the influence of various structure-forming agents, such as agar, pectin, gelatin, on the direction and rate of moisture transfer processes during storage of zefir samples. The possibility of using the method of infrared spectroscopy for assessing quality of structure-forming agents during incoming inspection is shown. The mass fraction of moisture in zefir made using agar decreased by 3.5% after 10 weeks of storage at a temperature of 18°C. During this period, the mass fraction of moisture in zefir made using pectin as a structure-forming agent decreased by 2.5%, while in zefir prepared on the basis of gelatin, the mass fraction of moisture decreased only by 1.2%. Thus, the addition of gelatin makes it possible to reduce the rate of moisture transfer by approximately 2–3 times. The low moisture transfer rate of zefir is due to the water-holding properties of the protein structure of gelatin. Diffusion coefficients were calculated to predict the rate of moisture transfer processes in zefir samples made using various structure-forming agents and stored at different temperatures. The lowest diffusion coefficient was determined in zefir made with the addition of pectin, while the highest diffusion coefficient was in the sample based on gelatin. However, zefir made from gelatin had the lowest actual moisture transfer rate, since the gradient of the water activity was minimal (7.6%). With an increase in the storage temperature of zefir made with the addition of various structure-forming agents from 18°C to 28°C, the rate of moisture transfer increased. In zefir produced on the basis of agar, this indicator increased by 2.7 times, in the sample from pectin by 3.0 times; in zefir based on gelatin by only 1.5 times. The results obtained make it possible to predict the risks of changes in zefir quality during storage.